Aesthetics of Artistic Creativity in the Haiku poeml ''Achour fenny as a model'' - خديجي , بشرى; chefiri, fatiha (El Omda in Linguistics and Discourse Analysis, 2025)
؟ If the Algerian poetic discourse, in its agreed-upon concept across the various historical periods, was able to prove its ability to contain topics that touch the poet's reality, and lie in the depth of his positions and literary visions, then the pens that wrote the haiku poem also expressed those topics, and formulated them in an intense and semantic poetic form. . Based on the topics of the haiku poem, which took a strict stance towards the aforementioned poetic imagination, we stop at the Algerian poet achour fanny in his book “Honalika Bayna Ghiyebayen Yahdetho an Naltaki”, in order to answer the following question: was what Ashour Fanny wrote that is included in the so-called haiku able to overcome the trap of metaphor? And imitation? Or is he still imprisoned in triple poetry and classicism, and if it is on the contrary, then what are the standards of poetry in his collection, which carried the banner of haiku in Algeria? ا